Administration of Bacterial Lipopolysaccharide during Early Postnatal Ontogenesis Induces Transient Impairment of Long-Term Synaptic Plasticity Associated with Behavioral Abnormalities in Young Rats - Tatyana Y. Postnikova; Alexandra V. Griflyuk; Julia L. Ergina; Olga E. Zubareva; Aleksey V. Zaitsev (MDPI AG, 2020)
Infectious diseases in early postnatal ontogenesis often result in cognitive impairments, particularly learning and memory. The essential foundation of learning and memory is long-term synaptic plasticity, which depends on N-methyl-D-aspartate (NMDA) receptors. In the present study, bacterial infection was modeled by treating rat pups with bacterial lipopolysaccharide (LPS, 25 µg/kg) three times, during either the first or the third week of life. These time points are critical for the maturation of NMDA receptors. We assessed the effects of LPS treatments on the properties of long-term potentiation (LTP) in the CA1 hippocampus of young (21−23 days) and adolescent (51−55 days) rats. LTP magnitude was found to be significantly reduced in both groups of young rats, which also exhibited investigative and motor behavior disturbances in the open field test. No changes were observed in the main characteristics of synaptic transmission, although the LTP induction mechanism was disturbed. In rats treated with LPS during the third week, the NMDA-dependent form of LTP was completely suppressed, and LTP switched to the Type 1 metabotropic glutamate receptor (mGluR1)-dependent form. These impairments of synaptic plasticity and behavior were temporary. In adolescent rats, no difference was observed in LTP properties between the control and experimental groups. Lastly, the investigative and motor behavior parameters in both groups of adult rats were similar.